The formation and development of the ownership regime through the constitutions of Vietnam - Nguyen, Quang Duc (Đại học Quốc gia Hà Nội, 2020)
The paper is to answer the question “What is the rule of the movement of the ownership regime in Vietnamese constitutions? Why?” Accordingly, the paper has fingered out that the ownership regime in Vietnam (on the policy scale) has developed in two contradictory directions, which is now continuing to diversify. The current direction is seen to be consistent with the demand of the market economy and the international trade integration of Vietnam. The study aims to emphasize the characteristics of the ownership regime in each period and explain why the ownership regime has such a developing tendency. The specific contents of the ownership regime are analyzed on the basis of the provisions of the Constitutions, laws and documents of the Communist Party of Vietnam. It is explained by the features of Vietnam’s institution in which every major policy is basically initiated from the political will of the Communist Party and such is highly likely to continue to be the mainstream trend in the future.